A new reverse mode light shutter from silica-dispersed liquid crystals. Issue 5 (9th April 2018) - De Filpo, Giovanni; Formoso, Patrizia; Mashin, Alexander I.; Nezhdanov, Aleksey; Mochalov, Leonid; Nicoletta, Fiore P.
ABSTRACT: Nanoparticle dispersions in liquid crystalline materials at low concentrations allow both investigating the formation of defects in liquid crystal (LC) and enhancing the light-scattering properties of LC optical devices. Reverse mode LC dispersions are LC devices, which look like transparent in their OFF state, when no electric field is applied, and opaque in their ON state. In this paper, a new reverse mode device, formed by a dispersion of a LC mixture in a silica nanoparticle crosslinked network, is presented. The morphology and the electro-optical properties of these silica nanoparticle/LC composites were investigated for two different LC mixtures with a negative dielectric anisotropy. The observed transmittances and relaxation times were found to depend strongly on the silica amount and chemical–physical properties of LC used in the sample preparation. GRAPHICAL ABSTRACT: